Development of a Liposomal Dosage Form Based on Hydrophobic Derivative of Indolocarbazole - B. Lugen; M. V. Dmitrieva; O. L. Orlova; I. I. Krasnyuk; I. I. Krasnyuk (jr.); D. O. Bokov; O. I. Stepanova; A. V. Belyackaya (Разработка и регистрация лекарственных средств, 2020)
Introduction. An original N-glycoside derivative of indolocarbazole LHS-1269 with a carbohydrate xylose residue was synthesized at the N.N. Blokhin Russian Cancer Research Center Ministry of Health of Russia. It is characterized by high antitumor activity against a number of transferable ascitic and solid tumors in vivo experiments. Due to the hydrophobic properties of the substance LHS-1269, a method of solubilization by encapsulation in phospholipid vesicles - liposomes is proposed for creating an injectable dosage form.Aim. Development of the composition of a model of a liposomal dosage form for injection of an indolocarbazole derivative LHS-1269.Materials and methods. Substance LHS-1269 (N.N. Blokhin Russian Cancer Research Center Ministry of Health of Russia), egg phosphatidylcholine (PC, E PC S, Lipoid, Germany), cholesterol >99 % (Sigma-Aldrich, Japan), polyethylene glycol-2000-distearoylphosphatidylethanolamine (PEG-PE, Lipoid, Germany). To prepare phospholipid vesicles, the method of lipid film hydration with subsequent filtration and extrusion was used. The obtained liposomes were analyzed using the method of spectrophotometry, laser scattering spectroscopy, the method of determining the electrophoretic mobility of particles, and viscometry.Results and discussion. On the basis of lipid components and active substance in various molar ratios, compositions were made and experimental models of liposomal dispersion were obtained. The compositions were evaluated based on the effectiveness of LHS-1269 incorporation into liposomes and physical and chemical parameters - dispersion viscosity, vesicle size distribution, and zeta-potential. As a result of the analysis of 7 studied compositions, the optimal molar ratios of the drug form components - LHS-1269/PC 1:160 and PC/cholesterol/PEG-PE 1:0.33:0.003 were determined. The use of this composition allows us to obtain relatively stable (zeta-potential -33 mV) homogeneous liposomes with a diameter of 190 nm with a maximum level of encapsulation of the active substance of 98 %.Conclusions. As a result of technological and chemical-pharmaceutical research, the composition of a model of a liposomal dosage form for injection of the indolocarbazole derivative LHS-1269 has been developed.